2023
DOI: 10.3390/d15050600
|View full text |Cite
|
Sign up to set email alerts
|

Global Diversity, Distribution, and Genetic Studies of Stable Flies (Stomoxys sp.)

Abstract: In the subfamily Stomoxyinae there are currently 18 recognized Stomoxys species, plus two subspecies. Most Stomoxys knowledge was gained through studies with S. calcitrans, a cosmopolitan species, economic pest, and vector. Other Stomoxys spp. are known only from a few trapped adult specimens. Herein, the Stomoxys spp. have been grouped by their ecological diversity, global distribution, and phylogeny and phylogeography. Seven species are dependent to some degree on humans and their activities, particularly an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…We identified three main species of Stomoxys, the two are the most dominant species in the African continent [24,25,42] however, Stomoxys species composition and density is location, season and methods of collection dependent. The equal attraction of Stomoxys to various livestock fur and four fabric colors that varies in wavelength from (400 -700nm) may demonstrate that Stomoxys visual system has a broader range of wavelength detection and tuning.…”
Section: Discussionmentioning
confidence: 99%
“…We identified three main species of Stomoxys, the two are the most dominant species in the African continent [24,25,42] however, Stomoxys species composition and density is location, season and methods of collection dependent. The equal attraction of Stomoxys to various livestock fur and four fabric colors that varies in wavelength from (400 -700nm) may demonstrate that Stomoxys visual system has a broader range of wavelength detection and tuning.…”
Section: Discussionmentioning
confidence: 99%
“…This season provides favorable environmental conditions for the emergence of the LSD vector populations that partly could explain the increase in LSD in local cattle populations in UP. Several previous studies have shown the role of mechanical vectors, such as Aedes, Culex, Anopheles mosquitoes, stable flies, and other biting arthropods, in the transmission of LSD [15,17,[35][36][37][38], and these vectors are abundant in UP [39][40][41][42], suggesting a connection between vector abundance and increase in LSD cases observed during these months.…”
Section: Discussionmentioning
confidence: 99%
“…Although improving the Nzi trap for stable flies was not an objective of this study, practical devices for the sampling or control of the many species of Stomoxys are of keen interest globally (Baldacchino et al 2018;Duvallet and Hogsette 2023). The new bi-level Nzi trap design was tested in an area with Stomoxys calcitrans only and performed as well as a standard Nzi trap.…”
Section: The Bi-level Nzi Trapmentioning
confidence: 99%